ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA KOPERASI KREDIT SANGOSAY CABANG PEMBANTU BAJAWA - So’o, Getrudis; Ismail, Nuraini; Marselina, Apriana (Jurnal Riset Ilmu Akuntansi, 2023)
The purpose of this study was to analyze the sources and uses of working capital in the Sangosay Credit Cooperative, Bajawa Sub-Branch. The type of research used in this research is descriptive research with data collection techniques (1) observation, (2) interviews, (3) documentation, (4) literature study. The results of the study show that, (1) in 2019-2020 the sources of working capital consist of several items, namely increasing principal savings, mandatory savings and increasing SHU/net surplus. The use of working capital consists of several items, namely the increase in office equipment, accumulated depreciation of equipment and reduced reserve funds. (2) 2020-2021 sources of working capital consist of several items, namely increasing principal savings, mandatory savings and reducing SHU/net surplus. The use of working capital consists of several items, namely increasing office equipment, accumulated depreciation of equipment and reduced reserve funds.